Diagnóstico de los riesgos laborales en los trabajadores del centro de acopio de almidón de yuca en el sitio Tarugo - Párraga Álava, Jasmina Margarita (2016)
The objective of this research was to diagnose occupational risks of employees Collection Center cassava starch in the Tarugo site Canton Chone, for knowledge of their work, for the development of this study the historical method that allowed for used an outline of information about occupational hazards, the field was conducted at the site of research to know the current situation of the company, the descriptive achievement detailing accidents caused by poor use of materials and work equipment the method of triple criterion is the qualitative identification matrix risk was developed in order to give a more reliable result on the magnitude of accidents, in conclusion, the study allowed us to understand the processes of each activity in the development cassava starch by a focused on promoting quality of life and safety of workers performing their tasks in an optimal physical, mental and social status through efficient diagnosis in risk management, reducing certain labor insecurities that generate accidents analysis work areas.